Evaluation of the implementation of integrative thematic learning: A qualitative research approach phenomenology - Fitri Indriani; Atiaturrahmaniah Atiaturrahmaniah (Graduate School, Universitas Negeri Yogyakarta, 2019)
This research aims at evaluating the implementation of integrative thematic learning. This research is an evaluation of the CIPP model with a qualitative approach phenomenology. Data were collected through observations, in-depth interviews, and documentation. The informants in the study were principals, teachers, and students. Data were analyzed using a qualitative method that is descriptive and critical. The results show that the implementation of integrative thematic learning in Muhammadiyah Suronatan Elementary School Yogyakarta has been carried out quite well, both in planning, implementation, and assessment of processes and learning outcomes. The implementation is success because it has been supported by excellent teachers' competence and adequate facilities and infrastructure supporting the learning process. Besides, teachers also have the motivation and spirit of learning. The implementation of integrative thematic learning of curriculum 2013 has a positive impact on student learning outcomes from both aspects of knowledge, attitude, and skills. From the knowledge aspect, the integrative thematic learning of the curriculum 2013 can deliver the best value to the national exam in the top 10 of Yogyakarta. The attitude aspect of the student spirit in learning shows an increase in students' confidence. As for the skill aspect, students become creative and innovative in both thinking and working. However, constraints are still found: handbooks for students have not been distributed equally by the government, and the lack of teachers' understanding of the way of the subject complaint that corresponds to the sub-theme.